Comparing the efficacy of chemiluminescence with lugol's iodine versus toluidine blue in the diagnosis of dysplasia in tobacco associated oral lesions - A diagnostic study - K V Swathi; G Maragathavalli; T N Uma Maheswari (Wolters Kluwer Medknow Publications, 2021)
Background: Chemiluminescence is the production of light as a result of a chemical reaction. Oral potentially malignant disorders (OPMDs) include both precancerous lesions and conditions that carry an increased risk of cancer. There are different etiological and risk factors for OPMDs such as smoking, alcohol consumption, infections such as viral and fungal, sun exposure and certain other genetic factors. The most common etiological factor for OPMDs is tobacco usage. Chemiluminescence is a light-based detection system and is very useful for detecting OPMDs for early intervention. Because it is a non-invasive procedure, it can be used to evaluate dysplastic changes in various OPMDs at their initial stage for timely intervention. Vital staining has also been used as a chair-side marker for delineating normal and dysplastic oral mucosal tissues. Aim: To compare the efficacy of chemiluminescence with Lugol's iodine to that with toluidine blue in diagnosing dysplastic changes in tobacco associated oral lesions. Methodology: A total of 84 patients with clinically suspicious oral mucosal lesions and OPMDs with tobacco habit history were included and randomly assigned to either of the diagnostic study groups (Group A: chemiluminescence with Lugol's iodine or Group B: chemiluminescence with toluidine blue). All these patients were subjected to a histopathological examination (reference standard). Results: The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and receiver operating characteristics (ROC) were 91.7%, 66.7%, 84.6%, 80%, and 0.792 for chemiluminescence with Lugol's iodine group (P = 0.001) respectively whereas for chemiluminescence with toluidine blue, the sensitivity, specificity, PPV, NPV and ROC were 100%, 60%, 93.3%, 100% and 0.800 (P = 0.002), respectively. Conclusion: The combination of chemiluminescence with toluidine blue had a better diagnostic efficiency in detecting dysplasia in tobacco-associated oral lesions when compared to the group of chemiluminescence with Lugol's iodine.